On the Classicism of “Non-classical” Psychology - Gennady G. Kravtsov; Oleg G. Kravtsov (Вестник Московского университета. Серия 14: Психология)
Background. The article discusses the current problem of the methodological foundations of psychological science. The article argues that the dangerous crisis for psychology, which was analysed by L.S. Vygotsky has not gone away, but moved from an acute form to a chronic one. “Methodological pluralism” in modern psychology is the triumph of blatant eclecticism. The authors see the main reason for the impasse which psychology has reached as the desire of this science to become like positive sciences from the field of natural science. Objective. The purpose of the article is to substantiate the point of view according to which L.S. Vygotsky created the only possible scientific psychology of the future, which will rightfully be classical. Method. The article discusses the fundamental principles and postulates of the cultural-historical approach, and outlines ways of research conceptualising the idea of a systemic and semantic structure of consciousness. Results. The authors analysed the methodological and philosophical foundations of psychological science. Based on the analysis carried out, the article highlights the approach proposed by L.S. Vygotsky. Conclusions. Comparison of the scientific fate of Galileo with the scientific fate of L.S. Vygotsky allowed the authors to assert that neither one nor the other discoverer of a fundamentally new method of comprehending reality had like-minded people during their lifetime. Their theoretical and methodological bar was raised too high, which made their work inaccessible to understanding by their contemporaries. The article concludes that the legacy of L.S. Vygotsky is not the historical past of psychological science, but its only possible and most promising future.